Beyond Historical Tragedy: The Frankfurt School and Judeo-Christian Messianism - Campbell, Colin J (Strategies of Critique, 2008)
In "Beyond Historical Tragedy" the author compares and discusses Hegel’s prescient understanding of the meaning of tragedy and how it differs from Aristotelian or quasi-Aristotelian theories. At the same time, he embarks on a critique of George Steiner’s Hegelian reading of Sophocles’ Antigone, and of tragedy more generally. He develops the idea that the Critical Theory of the Frankfurt School is closer to a Jewish or Christian perspective than to the tragic perspective - or to Hegel’s modern version of the tragic perspective. The contrast is most clear in the way that the idea of fate is negated by Adorno, Horkheimer, Marcuse and Benjamin.